Organizacija delovnega časa z vidika zahtev po večji fleksibilnosti - Senčur Peček, Darja (Delavci in delodajalci, 2009)
The contribution deals with the legislation covering regulations on working time in the Republic of Slovenia in the light of the possibilities it offers for introduction of flexible working time. It further presents additional possibilities for flexible forms of working time which could be laid down in collective agreements for individual sectors and finally the prevalence of diverse forms of working time practiced in the Republic of Slovenia in comparison to other European Countries.
Keywords: delovni čas; delovno pravo; fleksibilnost; izmensko delo; nadure; pravna ureditev